'Becoming more of myself': Safe sensuality, salsa and ageing. Issue 2 (May 2017) - Milton, Sarah
Ageing bodies are too often associated with invisibility or 'active' and 'successful ageing' discourses. Little research has focused on the daily and lived experiences of ageing, gender and sexuality in midlife, particularly when it comes to positive or more nuanced experiences. Based on ethnographic research in salsa classes with women in their fifties, this article explores the intersections and co-production of ageing, femininity and heterosexualities within particular spaces. Single women in midlife initially felt unsure of the 'rules of the road', out of place in social space. Salsa class spaces were produced as safe, alongside a 'safe sensuality' – which included embodying a glamorous salsa outfit but remaining respectfully feminine in 'age appropriate' ways. Participants navigated a way to become 'more' rather than 'less' of themselves with age, enjoying a 'second chance' which had not been afforded to the women of the generations before them. This article extends queer studies of space to account for ageing and for the (spatial) hierarchies embodied within heteronormativities.